Assessment of terminal drought tolerance among elite wheat (Triticum aestivum L.) genotypes using selected agronomic and physiological traits. (2nd April 2020) - Thungo, Zamalotshwa; Shimelis, Hussein; Odindo, Alfred O.; Mashilo, Jacob
ABSTRACT: The selection response of wheat ( Triticum aestivum L.) under water-limited condition can be enhanced through breeding novel genotypes possessing drought-adaptive and yield-related agronomic and physiological traits. The objective of this study was to evaluate terminal drought tolerance among bread wheat genotypes and select superior parents for breeding. Agronomic and physiological responses of 28 wheat lines were assessed under well-watered (WW) and terminal drought (TD) treatments using a 7 × 4 alpha-lattice design under rainout shelter (RS) and glasshouse (GH) environments. Significant ( p  ≤ 0.05) genotype × environment interaction effects were observed for number of days to heading (DTH), number of days to maturity (DTM), number of productive tillers per plant (TN), grain yield (GY), thousand kernel weight (TKW), stomatal conductance (SC), leaf canopy temperature (LCT) and chlorophyll content index (CCI) suggesting varied genotypic response under WW and TD treatments. Correlation analysis revealed significant associations TN and GY ( r  = 0.67; p  ≤ 0.001), TKW and GY ( r  = 0.72; p  ≤ 0.001), CCI and GY ( r  = 0.39; p  ≤ 0.05) under TD treatment. Drought tolerant wheat genotypes such as LM100, LM72, LM22 and LM95 are useful for direct cultivation and for developing breeding populations with enhanced yield performance.